Improvement of workers' biological indicators exposed to mercury at a gold refinery - Ramírez, Augusto V. (2011)
Background: Occupational exposure to mercury is associated to mercurialism, a characteristic occupational poisoning. To verify impact of environmental mercury levels improvement would have in gold's refinery workers of a Peruvian auriferous company, we carried out a reengineering program for exposure control. This program included health and hygiene occupational aspects and operation's management active participation. Objective: To study in gold refinery workers variations in indicators of exposure to mercury with environment labor quality improvement. Design: Prospective and descriptive study. Place of study: Occupational Health Service in a Peruvian mining company. Participants: Workers of gold refinery. Interventions: Modification of physician examination methodology, hygienic evaluation and improved conditions of the labor environment. Every six months we quantified the environmental limits of both toxic and biological exposure indicators. Then variation of exposure biological indices versus variation of environmental limits was analyzed. Main outcome measures: Environmental and biological indicators. Results: Environmental indicators values improved every year, as well as workers biological indicators. Environmental mercury decreased from 6.3 mg/m3 in 2003 to 0.03 at the end of 2007, p < 0.001. Urinary mercury decreased from 11.9 ug/L in 2003 to 2.3 in 2007, p < 0.01. Conclusions: In the group studied workers' toxic levels decreased with improvement of the environment indicator.